The intimate relationship as a site of social protection: Partnerships between people who inject drugs. (May 2017) - Rhodes, Tim; Rance, Jake; Fraser, Suzanne; Treloar, Carla
Abstract: Public health research treats intimate partnerships as sites of risk management, including in the management of HIV and hepatitis C transmission. This risk-infused biomedical approach tends to undermine appreciation of the emotional and socially situated meanings of care in intimate partnerships. In this article we explore qualitative interview accounts of the care enacted in partnerships between people who inject drugs, drawing on a 2014 study of 34 couples and 12 individuals living in two locations of Australia. A thematic analysis highlights 'best friend relationships', 'doing everything together', 'co-dependency', and 'doing normalcy' as core to narratives of care. As we will argue, the accounts position the care undertaken by couples as at once shaped by day-to-day practices of drug use and by social situation, with the partnership enacting care as a form of social protection, including protection from stigma and other environmental hostilities. The intimacy of doing everything together offers insulation against stigma, yet also reproduces its isolating effects. While the care produced in drug-using partnerships is presented as double-edged, we note how interview accounts are used to deflect the charge that these relationships represent harmful co-dependency. Taken together, the interview accounts negotiate a 'counter-care' in relation to normalcy, presenting the intimate partnership between people who use drugs as a legitimate embodiment of care. Highlights: Uses qualitative research to explore how care is enacted in intimate partnerships. Shows how drug-users' intimate partnerships act as sites of social protection. Finds that 'doing everything together' is a key dynamic of care of drug-using couples. Shows how drug users' partnerships negotiate tensions between care and harm. Advocates for a relational approach in understanding the dynamics of affective practices.